Torrefaction of Food Waste as a Potential Biomass Energy Source - Rahsya Nur Udzaifa Abdul Rahman; Mazni Ismail; Ruwaida Abdul Rasid; Noor Ida Amalina Ahamad Nordin (Indonesian Journal of Chemistry, 2019)
Food waste (FW) represents a major component of municipal solid waste (MSW) in Malaysia which causes negative impact due to poor waste management. One of a promising strategy to reduce the FW is to convert the FW to energy sources through thermal pre-treatment process which known as torrefaction. The aim of this study is to investigate the improvement of chemical properties and energy potential of the torrefied FW. The torrefaction of FW was conducted using tubular reactor to evaluate the influence of temperature (220 to 260°C) and residence time (15 to 60 min) on the quality of torrefied FW. The quality of torrefied FW were evaluated using ultimate analysis, proximate analysis, mass yield, energy yield and higher heating value (HHV). From ultimate analysis, the carbon, C was increased, however the hydrogen, H and oxygen, O decreased across the torrefaction temperature and residence time. This lead to the increasing of HHV with the increasing of temperature and time. The HHV of the dried FW was improved from 19.15 to 23.9 MJ/kg after being torrefied at 260°C for 60 min. The HHV indicated that FW has the potential to be utilized as an energy source.